The effects of tank colours on the growth and survival of cuttlefish (Sepia officinalis, Linnaeus 1758) hatchlings and juveniles - Sykes, António V. (2018)
The e¡ects of di¡erent tank colours (white, yellow sandy and black) on the growth, mortality and biomass production were studied for hatchling and early juvenile cuttle¢sh. For hatchlings, the use of di¡erent colour tanks did not promote di¡erences in growth due to the higher variability (standard deviation) found in the white- and sand-coloured tanks. Black tanks promoted the lowest and highest values for total mortality and biomass respectively. For juveniles, the use of di¡erent tank colours promoted di¡erent growth (Po0.05), but not mortality. Black tanks promoted the best results in terms of growth and biomass. The results obtained in the present study advise the use of black (or dark colour) tanks in the hatchling and early juvenile stages to reduce the standard deviations associated with growth, mortality and biomass production. This will contribute to minimize problems associated with slow and fast growers and competition.